Science translated : Latin and vernacular translations of scientific treatises in medieval Europe - Goyens, Michèle; De Leemans, Pieter; Smets, An (Mediaevalia Lovaniensia, 2008)
Medieval translators played an important role in the development and evolution of a scientific lexicon. At a time when most scholars deferred to authority, the translations of canonical texts assumed great importance. Moreover, translation occurred at two levels in the Middle Ages. First, Greek or Arabic texts were translated into the learned language, Latin. Second, Latin texts became source-texts themselves, to be translated into the vernaculars as their importance across Europe started to increase. The situation of the respective translators at these two levels was fundamentally different.